Analysis of the Organization and Response to Influenza Vaccination in Slovenia and Europe - Bračko, Brina; Arnič, Maja (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Influenza is one of the biggest seasonal challenges every year. Many people get sick, but the more severe course is more typical for the elderly population and chronically ill patients, young children, pregnant women and overweight people. Every year, an updated or improved vaccine is available against it. Many people decide to get vaccinated, but the response rate could still be much better. The aim of this article is to analyze the response rate to vaccination among individual age groups in Slovenia and Europe and look to the future, the possibilities for progress and the continuation of good work.